2012
DOI: 10.1007/s00266-012-9890-5
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Noninterventional Study of the Treatment of the Aging Hand with Juvéderm Ultra® 3 and Juvéderm® Hydrate

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors at www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…As more patients undergo facial rejuvenation treatments, discrepancies in the appearance of a youthful face and aged hands may become bothersome and reveal a patient's true age. 2 , 6 Accordingly, greater numbers of aesthetically aware patients are seeking hand rejuvenation treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As more patients undergo facial rejuvenation treatments, discrepancies in the appearance of a youthful face and aged hands may become bothersome and reveal a patient's true age. 2 , 6 Accordingly, greater numbers of aesthetically aware patients are seeking hand rejuvenation treatments.…”
mentioning
confidence: 99%
“…Several treatments are used to restore lost volume and minimize the appearance of veins and tendons in the hand, including injectable hyaluronic acid, 6 poly- l -lactic acid, 7 and calcium hydroxylapatite 8 ; autologous fat transfer 2 ; vein treatment (sclerotherapy) 2 ; chemical peels 2 ; and laser and light therapies. 2 One photonumeric scale has been validated for photographic 9 and live-subject 10 assessments of the severity of hand aging.…”
mentioning
confidence: 99%
“…It has also been commonly used as a debriding topical agent for wound care [14]. FDA approved hyaluronic acid based dermal fillers have also been safely employed for reconstructive reasons [15-17]. However, of all the procedures mentioned, autologous fat grafting has the longest track record of use well prior to the advent of modern medicine [18].…”
Section: Discussionmentioning
confidence: 99%
“…Both the investigators and the patients reported a significant aesthetic improvement. 36 However, these agents are not currently available in the United States. Another study looked at long-term effectiveness of small gel particle (SGP)-HA for the hands in 16 patients.…”
Section: Hyaluronic Acidmentioning
confidence: 99%